PENGARUH NILAI TUKAR RUPIAH TERHADAP KESEJAHTERAAN PETANI DI KALBAR - B0111107, Gamolius Donatus Eko NI Donatus Eko (Jurnal Pembangunan dan Pemerataan, 2016)
ABSTRACT This research title is "Effect of rupiah against the welfare of farmers in West Kalimantan". This study aims to determine the effect of exchange rate changes Rupiah (against US dollar) to improving the welfare of farmers in general and in the agriculture sector in West Kalimantan. The data used in this research is secondary data. Data taken based on time series in the form of a monthly from 2008-2013. This study uses descriptive quantitative approach using simple regression models, as well as the F test and t test to test the hypothesis of whether the exchange rate (against US dollar) influence on the welfare of farmers in West Kalimantan. The results showed that the exchange rate significantly and negatively impact on the level of general well-being of farmers in West Kalimantan. At the level of welfare of farmers in the agricultural subsector, plantation crops significant and negative effect on people, but in contrast to the level of welfare of farmers in horticultural crops significant and positive impact. Keywords: exchange rate, and the welfare of farmers